Геральдичний декор в архітектурі Львова кінця XVI – початку XXI ст. - Шукатка Мар’яна Степанівна (Національний університет "Львівська політехніка", 2018)
Дисертаційна робота присвячена дослідженню геральдичного декору в архітектурі Львова. Геральдичний декор доповнює архітектурний образ будівлі і є важливим елементом композиції. У результаті натурних обстежень проведено інвентаризацію геральдичного декору на фасадах будівель. Досліджено збережені та втрачені зразки геральдичного декору в архітектурі Львова. Визначено основні типи будівель та види гербів, якими вони декорувались. Встановлено способи розміщення геральдичного декору в архітектурі. Проведено класифікацію елементів геральдичного декору та їх поєднання в геральдичні композиції, а також стилістичний аналіз. У роботі сформульовано принципи застосування геральдичного декору в архітектурі та рекомендації для реставрації. Визначено перспективи для подальших досліджень геральдичного декору в архітектурі. Диссертационная работа посвящена исследованию геральдического декора в архитектуре Львова. Геральдический декор дополняет архитектурный образ здания и является важным элементом композиции. В результате натурных обследований проведена инвентаризация геральдического декора на фасадах зданий. Исследованы сохраненые и утраченные образцы геральдического декора в архитектуре Львова. Определены основные типы зданий и виды гербов которыми они декорировались. Установлено восемь способов размещения геральдического декора в архитектуре. Проведена классификация элементов геральдического декора и их сочетания в геральдические композиции, а также стилистический анализ. В работе сформулированы принципы применения геральдического декора в архитектуре и рекомендации для реставрации. Определены перспективы для дальнейших исследований геральдического декора в архитектуре. The thesis is devoted to the study of heraldic decoration in Lviv architecture. Architectural decoration is an integral part of the facade of the building and its composition. Heraldic decor complements the architectural image of the building and is an important part of the composition. This type of decor is an integral part of the visual historical-architectural identification in the public space of the city. It indicates the status of institutions, owners and building founders. The heraldic decoration carries an additional semantic load and serves as a marker on the facade of the building. It reflects the history of the city and the state, its role is more important than the usual architectural decoration. Heraldic decoration was explored only in historical works, heraldry, ornamental art and wasn’t considered as a architectural component. In the work was investigated literature about using of heraldic decor in the architecture of Europe, Ukraine and Lviv. In process of field studies 120 buildings in Lviv with heraldic décor were investigated and was created catalog of inventory cards. Were analyzed retained and lost samples of heraldic decor. Objects with heraldic decoration were divided by function, based on the classification of buildings and structures. This separation allowed to identify the main types of buildings decorated with emblems and establishing a relationship between the type of building and the kind of heraldic decor. Types of heraldic decor are defined as: with state, urban, corporate, church and personal symbols. Were identified eight ways of placing the heraldic decoration in architecture: first way – it tops up pediments, attics, porticoes, tongs; the second way - placed on the wall; the third way - placed above the entrance of the building; the fourth way- decorates the windows; the fifth way – in metal balconies fenced; the sixth way - decorates columns or pilasters; the seventh way - decorates the tower; the eight way- in the facade sculpture. Was investigated structure of the facades proportions decorated with heraldic decor. Heraldic figures are placed on shields of various shapes or arranged in frames and architectural elements. Heraldic compositions are divided into several groups:1) heraldic figure is placed without a shield just on the sparse walls; 2) heraldic figure is placed in the framing; 3) heraldic figure is placed on a round shield or in the wreath; 4) heraldic figure placed on a shield without any décor; 5) heraldic figure is placed on a shield and is topped with a helmet or krown; 6) heraldic figure is placed on the mantle and is topped with a miter; 7) heraldic figure is placed on the shield and ornamented with floral decoration; 8) heraldic figure is placed on the shield ornamented with floral decoration, crown or helmet; 9) heraldic figure is located on a shield held by the supporters; 10) heraldic figure is placed on a shield with a crown which is held by the supporters. Is carried out the stylistic analysis of the heraldic decoration on the building facades. Using of heraldic compositions as an element of the decor of the building depends on the style that dominated one or another period in the architecture of Lviv. The paper formulates six principles of application of heraldic decoration in architecture: typological dependence, compositional unity, accentuation, semantic dependence, unity of form and content, stylistic subordination. The state of conservation of heraldic decoration is investigated and the main causes of destruction of heraldic decoration are determined. Has been developed an algorithm for restoration on the example of three samples restoration of heraldic decoration. The stages of restoration of the heraldic decoration are defined: purification, polychromy study, desalination, biocide treatment, stone strengthening, gluing, addition and reproduction of lost elements, toning, hydrophobization. Are determined prospects for further study of heraldic decor in architecture. Was discovered that heraldic decoration in interior, memorial and sacred architecture, on small architectural forms in Lviv had not been investigated. It is proposed to create a "Lviv Magistrate Museum" where the dismantled heraldic decor will be stored. The study of emblem in the decoration of Ukraine castles is also promising. Heraldic decoration is an integral element of buildings, since its application is followed during all periods of architectural formation of the city.
Геральдический декор в архитектуре Львова конца XVI – начала XXI в.
Heraldic decoration in the Lviv architecture the end of XVI – early XXI centuries
Keywords: геральдичний декор; фасади будівель; архітектурний декор; герб; геральдический декор; фасады зданий; архитектурный декор; герб; heraldic decoration; facades of buildings; architectural design; emblem; 72:7.025.4:929.6(477.83) «XVI-XXI»